Maternal mental health problems during pregnancy and associations with childhood asthma and food allergy - Cooklin, A R; Giallo, Rebecca; Kozyrskyj, Anita; Nicholson, Jan (My University, 2013)
Antenatal maternal distress has been associated with a range of health and wellbeing problems in children. This study specifically investigated the relationship between antenatal mental health difficulties, asthma and food allergy in a nationally representative sample of Australian children. Participants were 4226 children and their biological mothers from the infant cohort of the Longitudinal Study of Australian Children (LSAC). Mothers reported on antenatal mental health difficulties, and whether their child had experienced wheeze or whistling in the chest, on-going food or digestive allergies, or been diagnosed with asthma when aged 0-12 months, 2-3 years, 4-5 years and 6-7 years. Approximately 19% of mothers reported antenatal mental health difficulties. After adjusting for known factors associated with asthma and allergy, antenatal mental health difficulties were associated with an increased risk of wheeze at age 0-12 months (OR, 1.34; 95%CI, 1.07-1.67) and 2-3 years (OR, 1.38; 95%CI, 1.13-1.69), as well as allergies at age 0-12 months (OR, 1.45 95%CI, 1.00-2.08). Asthma was 1.5 times more likely at age 4-5 and 6-7 years following antenatal mental health difficulties (OR, 1.45; 95%CI, 1.15-1.83 and OR, 1.45: 95%CI, 1.18-1.77, respectively). Finally, wheeze and asthma that was persistent across childhood was 1.4 times more likely for children of mothers who had antenatal mental health problems (OR, 1.37; 95%CI, 1.00 -1.89 and OR, 1.35: 95%CI, 1.04-1.75, respectively). These data implicate antenatal mental health difficulties in the development of childhood asthma and food allergy. Implications for policy and practice focussed on antenatal mental health screening and support will be discussed.
Keywords: Families -- Mothers; Health -- Mental; Families and relationships; Health and wellbeing; Health; Families; Mothers; Mental; Health and wellbeing; Families and relationships